2007
DOI: 10.1002/cbic.200600446
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Sugar Phosphate Cyclase Superfamily Involved in Primary and Secondary Metabolism

Abstract: Sugar Phosphate Cyclases (SPCs) catalyze the cyclization of sugar phosphates to produce a variety of cyclitol intermediates that serve as the building blocks of many primary metabolites, e.g., aromatic amino acids, and clinically relevant secondary metabolites, e.g., aminocyclitol/ aminoglycoside and ansamycin antibiotics. Feeding experiments with isotopically-labeled cyclitols revealed that cetoniacytone A, a unique C 7 N-aminocyclitol antibiotic isolated from an insect endophytic Actinomyces sp., is derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
86
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…Prior to the anemone manuscript, Wu et al reported a phylogenetic analysis of bacterial and fungal DHQS-like enzymes that led to the discovery that the enzymes group according to their substrates and products. [7] Although many of the DHQS proteins clustered into distinct families representing known compounds, the authors also identified a mystery family from cyanobacteria and fungi, for which no products were known. A major advance from this manuscript was the delineation of active-site-lining residues that were important for selectivity.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Prior to the anemone manuscript, Wu et al reported a phylogenetic analysis of bacterial and fungal DHQS-like enzymes that led to the discovery that the enzymes group according to their substrates and products. [7] Although many of the DHQS proteins clustered into distinct families representing known compounds, the authors also identified a mystery family from cyanobacteria and fungi, for which no products were known. A major advance from this manuscript was the delineation of active-site-lining residues that were important for selectivity.…”
mentioning
confidence: 97%
“…DHQS-like enzymes lead to the synthesis of many different products, including DHQ, the predicted precursor of MAAs such as shinorine. [7] However, a recent study shows that 4-deoxygadusol is synthesized directly by a DHQS-like enzyme. [3] [a] Prof. E. W. [8] A comparative informatics method was employed.…”
mentioning
confidence: 99%
“…The new pathway gave a unique C 2 -C 2 -C 3 labeling pattern in the C 7 N moiety as opposed to the characteristic C 3 -C 4 correlation of the shikimate pathway (Scheme 10). Although the initial results shed some light on the biosynthetic origin of acarbose (50) and validamycin A (51), it was not until more recent experimental evidence emerged to support the existence of alternate biosynthetic pathways involving 2-epi-5-epivaliolone (59) as a common intermediate.…”
mentioning
confidence: 98%
“…44 The C 7 N-aminocyclitol-containing natural products, 45 e.g. acarbose (50), validamycin A (51), cetoniacytone (52), and pyralomicin (53), were initially considered to be the aliphatic version of the aromatic C 7 N-units found in many antibiotic natural products, e.g. rifamycin (54), mitomycin (55), and geldanamycin (56) (Scheme 9), which are derived from the aminoshikimate pathway -a metabolic pathway parallel to the shikimate pathway.…”
mentioning
confidence: 99%
“…8) At the same time, (Ϫ)-2 has recently become an attractive subject for biochemists due to its unusual biosynthetic pathway. [9][10][11][12] Determination of the absolute configuration could provide useful information on its medicinal purpose as well as biosynthetic study.…”
mentioning
confidence: 99%